Nestin Protein Is Phosphorylated in Adult Neural Stem/Progenitor Cells and Not Endothelial Progenitor Cells - Jun Namiki; Sayuri Suzuki; Takeshi Masuda; Yasushi Ishihama; Hideyuki Okano (Hindawi Limited, 2012)
An intermediate filament protein, Nestin, is known as a neural stem/progenitor cell marker. It was shown to be required for the survival and self-renewal of neural stem cells according to the phenotypes of Nestin knockout mice. Nestin expression has also been reported in vascular endothelial cells, and we recently reported Nestin expression in proliferating endothelial progenitor cells, but not in mature endothelial cells. Using quantitative phosphoproteome analysis, we studied differences in phosphorylation levels between CNS Nestin in adult neural stem cells and vascular Nestin in adult bone-marrow-derived endothelial progenitor cells. We detected 495 phosphopeptides in the cell lysates of adult CNS stem/progenitor cells and identified 11 significant phosphorylated amino acid residues in the Nestin protein. In contrast, endothelial progenitor cells showed no significant phosphorylation of Nestin. We also measured neoplastic endothelial cells of the mouse brain and identified 13 phosphorylated amino acid residues in the Nestin protein. Among the 11 phosphorylated amino acids of adult CNS Nestin, five (S565, S570, S819, S883, and S886) were CNS Nestin-specific phosphorylation sites. Detection of the CNS-specific phosphorylation sites in Nestin, for example, by a phospho-specific Nestin antibody, may allow the expression of CNS Nestin to be distinguished from vascular Nestin.